Restoring the biological activity of crizanlizumab at physiological conditions through a pH-dependent aspartic acid isomerization reaction - Fabian Bickel; François Griaud; Wolfram Kern; Frieder Kroener; Manuela Gritsch; Jérôme Dayer; Samuel Barteau; Blandine Denefeld; Chi-Ya Kao-Scharf; Manuel Lang; Izabela Slupska-Muanza; Carla Schmidt; et al. (mAbs)
In this study, we report the isomerization of an aspartic acid residue in the complementarity-determining region (CDR) of crizanlizumab as a major degradation pathway. The succinimide intermediate and iso-aspartic acid degradation products were successfully isolated by ion exchange chromatography for characterization. The isomerization site was identified at a DG motif in the CDR by peptide mapping. The biological characterization of the isolated variants showed that the succinimide variant exhibited a loss in target binding and biological activity compared to the aspartic acid and iso-aspartic acid variants of the molecule. The influence of pH on this isomerization reaction was investigated using capillary zone electrophoresis. Below pH 6.3, the succinimide formation was predominant, whereas at pH values above 6.3, iso-aspartic acid was formed and the initial amounts of succinimide dropped to levels even lower than those observed in the starting material. Importantly, while the succinimide accumulated at long-term storage conditions of 2 to 8°C at pH values below 6.3, a complete hydrolysis of succinimide was observed at physiological conditions (pH 7.4, 37°C), resulting in full recovery of the biological activity. In this study, we demonstrate that the critical quality attribute succinimide with reduced potency has little or no impact on the efficacy of crizanlizumab due to the full recovery of the biological activity within a few hours under physiological conditions.